KETERAMPILAN PROSES SAINS SEBAGAI HASIL PEMBELAJARAN BIOLOGI MATERI JARINGAN SEL TUMBUHAN BERBASIS KEGIATAN LABORATORIUM - Vincencia Ambar Cahyaningsih; Agus Sujarwanta; Anak Agung Oka (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2024)
Biology is a science related to finding out and studying aspects of the life of living creatures in the universe. Biology does not only contain concepts or theories but also includes processes and attitudes, all of which need to be developed. The aims of this research are 1) to determine the science process skills in the Plant Cell material of Yos Sudarso Metro High School students. 2) to determine the difficulty of science process skills in Plant Cell material for Yos Sudarso Metro High School students. The subjects of this research were class Data collection was carried out using observation sheets to assess science process skills during research activities based on practical activities and learning outcomes using written evaluation tests with multiple choice questions. The results of this research are in the form of science process skills and the difficulties experienced by students during learning, namely: (1) the form of skill in each indicator of science process skills is (a) Skills in using tools and materials, being able to use tools and materials well and being able to say the function of the microscope part is 36.6%. (b) in the observation skills of students who can observe objects well and accurately mention cell organelles and their functions by 10%. (c) in communication skills that can convey the results obtained accurately and completely by 0.3%. (2) the form of difficulty experienced by students for each question on plant cell material, namely: (a) the average percentage of difficulty experienced by students in completing the name of the inventor of the cell is 10%. (b) The average percentage of difficulties experienced by students in completing cell organelle analysis is 25.2%. (c) The average percentage of difficulties experienced by students in completing analyzing the function of cell organelles is 21.6%.